Optimal design of metal forming die surfaces with evolution strategies - Schenk, Olaf; Hillmann, Matthias (Computers & structures, 2004)
A common characteristics in the simulation of automotive sheet metal forming processes is that nearly all die surfaces are manually created within conventional computer-aided design systems (CAD). The solutions produced using these CAD systems are undoubtedly valuable from the point of view of applicability in sheet metal forming practice. However, this approach is time consuming and most of the design time is spent within these CAD systems. This paper presents the development of a computer-based approach for the evolutionary automatic design (EAD) of geometry and process parameters for industrial metal forming processes. The main characteristics of the solution methodology are the use of evolution strategies within the optimizer, the use of sheet metal formability as objective functions and a parameterization of die surfaces. The results of a comparative study of our EAD die surface generation against conventional CAD die surface generation for a representative structural design problem show the efficiency of the former. It is observed that EAD often finds the region of the search space containing the global optimum, thus supporting engineers in practice with automatic generated sheet metal forming tools.